Could a walrus play the saxophone? and other questions about animals - Mason, Paul (Chicago, Illinois Raintree, 2014)
Answers various questions kids have about animals
a gift from book africa
1 2 13 15
Keywords: Animals -- Miscellanea -- Juvenile literature; Animals -- Miscellanea; Questions and answers